Performance evaluation of the semiconductor industry based on a metafrontier approach - Chiu, Ching-Ren; Fang, Chen-Ling; Tsang, Seng-Su; Chen, Yi-Fen (Technological and economic development of economy, 2018)
The semiconductor industry has been regarded as one of the most important industries by Taiwan due to the market share of Taiwan’s semiconductor industry in 2011 ranked second worldwide. However, the European debt crisis triggered a global economic recession in 2011, causing Taiwan’s output of semiconductors in 2010 and 2011 to show negative growth. This paper will mainly explore, from the performance evaluation perspective, the Malmquist productivity index of the Taiwan’s semiconductor industry based on a metafrontier approach. The empirical results show that the European debt crisis in 2011 had an impact on Integrated circuit (IC) design companies and IC manufacturing companies, but that there was no influence on IC packaging and testing companies when measuring static efficiency. From the viewpoint of dynamic productivity performance, the paper finds that the main reason for the negative growth of IC packaging and testing companies and IC design companies came from a backward movement in technical change, but the main reason for the negative growth of IC manufacturing companies derived from a decline in pure technical efficiency.